Advanced Nanotechnologies for Detection and Defence against CBRN Agents (Dordrecht : Springer Netherlands, 2018)
This volume gives a broad overview of advanced technologies for detection and defence against chemical, biological, radiological and nuclear (CBRN) agents. It provides chapters addressing the preparation and characterization of different nanoscale materials (metals, oxides, glasses, polymers, carbon-based, etc.) and their applications in fields related to security and safety. In addition, it presents an interdisciplinary approach as the contributors come from different areas of research, such as physics, chemistry, engineering, materials science and biology. A major feature of the book is the combination of longer chapters introducing the basic knowledge on a certain topic, and shorter contributions highlighting specific applications in different security areas.
47, P. Písařík , M. Jelínek, J. Remsa, J. Mikšovský: Antibacterial Coatings for Biomedical Applications -- Chap. 48, I.V. Pavlidis: Identification and Evolution of Biocatalysts of Interest -- Chap. 49, T.S. Kavetskyy, R.I. Khalilov, O.O. Voloshanska, L.M. Kropyvnytska, T.M. Beyba, V.A. Serezhenkov, A.N. Nasibova, A. Akbarzadeh, S.Ya. Voloshanska: Self-organized Magnetic Nanoparticles in Plant Systems: ESR Detection and Perspectives for Biomedical Applications -- CHAP. 50, N. Enaki, T. Paslari, E. Starodub, S. Bizgan, C. Ristoscu, I.N. Mihailescu, A. Vaseashta: Nanoparticle Based Decontamination of Bacteria/Pathogens -- CHAP. 51, A. Stoilova, A. Georgiev, D. Nazarova, L. Nedelchev, D. Dimov, P. Petkov: Development of Nanostructured Materials with CBRN Agents Sensing Properties -- Subject Index.
Physics and Astronomy
text file PDF
Keywords: Nanoscale science; Nanoscience; Nanostructures; Nanotechnology; Materials science; System safety; Nanochemistry